Exurbia now : the battleground of American democracy - Masciotra, David (Melville House, 2024)
"The suburbs have become too liberal and diverse for many white American conservatives, so "exurbia"--areas outside the cities and their suburbs--are becoming the staging ground for the radical right extremist insurgency..."--